2016
DOI: 10.1111/hepr.12705
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of recurrent hepatocellular carcinoma after radiofrequency ablation

Abstract: Radiofrequency ablation (RFA) is effective for the local control of hepatocellular carcinoma (HCC), particularly when a patient's liver functional reserve does not allow radical resection. There is controversy regarding the superiority of surgical resection compared with RFA for such patients, particularly those with three or fewer tumors with diameters ≤3 cm. Moreover, HCC often recurs after RFA, and the tumor cells show distinct phenotypic changes. Incomplete ablation accounts for tumor recurrence, and recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 56 publications
(99 reference statements)
0
36
0
Order By: Relevance
“…Hepatocellular carcinoma occurs in the background of chronic hepatitis or cirrhosis, which leads to frequent recurrence after curative therapy. In fact, patients with HCC have a high risk of tumor recurrence even after local curative treatment by either surgical resection or RFA . The recurrence rate of HCC is 15–30% within 1 year, and approximately 80% in 5 years, even after curative therapy .…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma occurs in the background of chronic hepatitis or cirrhosis, which leads to frequent recurrence after curative therapy. In fact, patients with HCC have a high risk of tumor recurrence even after local curative treatment by either surgical resection or RFA . The recurrence rate of HCC is 15–30% within 1 year, and approximately 80% in 5 years, even after curative therapy .…”
Section: Introductionmentioning
confidence: 99%
“…A subset of HCC; that is, tumors expressing biliary/stem cell markers (including keratin 19 [KRT19, also known as cytokeratin 19, K19, or CK19] and sal‐like protein 4) or those with a high proliferative activity, shows rapid tumor growth and a high metastatic rate, whereas most HCCs grow relatively slowly and are often treatable even after disease recurrence. Sorafenib, a multikinase inhibitor, is widely used as the first‐line treatment for advanced HCC, especially HCC with extrahepatic spread or vascular invasion, although the antitumor effects are insufficient for controlling large and multinodular HCC, and for preventing tumor recurrence in the surrounding inflamed liver after treatment . Other types of multikinase inhibitors have also proven effective against unresectable HCC, thereby underscoring the importance of signaling pathways triggered by tyrosine kinase receptors in the progression of HCC, which has a potential for promising new targeting therapies for HCC .…”
Section: Introductionmentioning
confidence: 99%
“…Sorafenib, a multikinase inhibitor, is widely used as the first-line treatment for advanced HCC, especially HCC with extrahepatic spread or vascular invasion, [5][6][7] although the antitumor effects are insufficient for controlling large and multinodular HCC, and for preventing tumor recurrence in the surrounding inflamed liver after treatment. 8,9 Other types of multikinase inhibitors have also proven effective against unresectable HCC, 10-12 thereby underscoring the importance of signaling pathways triggered by tyrosine kinase receptors in the progression of HCC, which has a potential for promising new targeting therapies for HCC. 13 However, biomarkers that can predict the response of HCC to these targeted therapies are currently unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…Intratumoral hypoxia followed by stabilization of hypoxia-inducible factor (HIF)-1α promotes acquisition of EMT-like features in various kinds of carcinomas (2, 9, 11, 18) as well as hematopoietic tumors (1). Several studies have reported that HIF-1α overexpression is positively correlated with EMT induction in hepatocellular carcinoma (HCC) cell lines and surgical resection specimens (7,8,20). In addition, hypoxia-induced EMT resulted in multidrug resistance in HCC cells (16), tumor metastasis after transcatheter arterial embolization (TAE) (4), and poor prognosis in HCC patients (6).…”
Section: Introductionmentioning
confidence: 99%